The Burden of Hand Injuries at a Tertiary Hospital in Sub-Saharan Africa - Makobore, P.; Galukande, M.; Kalanzi, E.; Kijjambu, S. C. (Emergency Medicine International, 2015)
Background. Hand injuries are common worldwide and lead to heavy financial losses in terms of treatment, job loss, and time off duty. There is paucity of data on hand injuries in sub-Saharan Africa. The aim of this study was to determine the burden and early outcomes of hand injuries at a tertiary hospital. Method. A descriptive prospective study. Eligible patients were recruited over 5 months and followed up for four weeks. Pain, nerve function, and gross functions of the hand were assessed. Results. In total 138 patients were enrolled out of 2940 trauma patients. Of these, 122 patients returned for follow-up. The majority of the patients were males (83%). Mean age was 26.7 years (SD 12.8). The commonest places of injury occurrence were the workplace (36%), home (28%), and on the road (traffic crushes) (23%). Machines (21.3%) were the commonest agent of injuries; others were knives (10%) and broken glass (10%). Sixty-three (51%) patients still had pain at one month. Conclusions. Hand injuries accounted for 4.7% of all trauma patients. Road traffic crushes and machines were the commonest causes of hand injuries. Men in their 20s were mostly involved. Sensitization for prevention strategies at the workplace may be helpful.